Fire in the Wildland-Urban Interface: Preparing a Firewise Plant List for WUI Residents - Anna L. Behm; Alan J. Long; Martha C. Monroe; Cotton K. Randall; Wayne C. Zipperer; Leslie Annie Hermansen-Baez (EDIS, 2004)
This extension publication is a guide to making a firewise plant list to assist local homeowners with firewise landscaping. It includes a step-by-step method for determining whether or not a particular plant is appropriate for firewise landscaping. Extension agents, nursery personnel, landscape architects, or urban foresters may use this publication for preparing local firewise plant lists in the wildland-urban interface (WUI). These lists can be combined with the Florida Cooperative Extension Service publication “Selecting and Maintaining Firewise Plants” for homeowners and other interested groups. This document is Circular 1453, one of the Fire in the Wildland-Urban Interface series of the School of Forest Resources and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: July 2004.